Pengembangan E-Modul Berbasis Somatic, Auditory, Visual And Intellectual (SAVI) Terhadap Kemampuan Penalaran Matematis Pada Materi Geometri - Ria Deswita; Wulandari Wulandari; Nur Rusliah (Departement of Mathematics Education, 2022)
Abstract This research is motivated by the importance of geometry, geometry is a very important thing to learn, especially in mathematics. Therefore students must learn geometry The truth reveals that geometry students still have limited mathematical reasoning abilities. . A learning module that can assist pupils in learning geometry is necessary in order to overcome these challenges.. Therefore, E module based on Somatic, Auditory, Visual and Intellectual (SAVI) was developed. The goal of this research is to develop e-module based on SAVI on geometry subject. This study employs the Plomp development model and is a development study. The subject are nine grade students of SMP N 2 Kerinci. The instruments used were validation sheets and teacher and student response questionnaires. Based on data analysis, it was found that (a) the developed SAVI-based e-module was valid both in terms of material and appearance, (b) the developed SAVI-based e-module met very practical criteria both in terms of presentation efficiency, attractiveness, ease of use, and design with a percentage of 85.6% based on student response questionnaires, and 76.8% based on teacher response questionnaires.